Caspase-3: A Vulnerability Factor and Final Effector in Apoptotic Death of Dopaminergic Neurons in Parkinson's Disease - Hartmann, Andreas; Hunot, Stéphane; Michel, Patrick P.; Muriel, Marie-Paule; Vyas, Sheela; Faucheux, Baptiste A.; Mouatt-Prigent, Annick; Turmel, Hélène; Srinivasan, Anu; Ruberg, Merle; Evan, Gerard I.; Agid, Yves; et al. (Proceedings of the National Academy of Sciences - PNAS, 2000)
Caspase-3 is an effector of apoptosis in experimental models of Parkinson's disease (PD). However, its potential role in the human pathology remains to be demonstrated. Using caspase-3 immunohistochemistry on the postmortem human brain, we observed a positive correlation between the degree of neuronal loss in dopaminergic (DA) cell groups affected in the mesencephalon of PD patients and the percentage of caspase-3-positive neurons in these cell groups in control subjects and a significant decrease of caspase-3-positive pigmented neurons in the substantia nigra pars compacta of PD patients compared with controls that also could be observed in an animal model of PD. This suggests that neurons expressing caspase-3 are more sensitive to the pathological process than those that do not express the protein. In addition, using an antibody raised against activated caspase-3, the percentage of active caspase-3-positive neurons among DA neurons was significantly higher in PD patients than in controls. Finally, electron microscopy analysis in the human brain and in vitro data suggest that caspase-3 activation precedes and is not a consequence of apoptotic cell death in PD.